Chimeric RNA-binding protein-based killing switch targeting hepatocellular carcinoma cells - Jiong Yang; Shigang Ding (Elsevier, 2021)
Cancer cell-specific killing switches are synthetic circuits developed as an intelligent weapon to specifically eliminate malignant cells. RNA-delivered synthetic circuits provide safer means to control oncolytic functions, in which proteolysis-responding capsid-cNOT7 is developed to enable logic computation and modular design. Unfortunately, although circuits containing these capsid-cNOT7s exhibited good performance when introduced as replicons, in modified mRNA (modRNA) delivery, the performance was not quite as good. To improve this situation, alternative modules suitable for modRNA delivery need to be developed. An attractive option is RNA-binding protein (RBP)/riboswitches. In this study, RBPs were engineered by fusing with degron and cleavage sites. The compatibility of these chimeric RBPs with proteolysis-based sensing units were tested. Eight two-input logic gates and four three-input logic gates were implemented. After building this chimeric RBP-based system, we constructed a hepatocellular carcinoma (HCC) cell-specific killing circuit using two proteolysis-based sensing units, a two-input logic OR gate, and a leakproof apoptosis-inducing actuator, which distinguished HCC cells and induced apoptosis in a mixed IMR90-PLC/PRF/5 population.